CORRELATION BETWEEN NEUTROPHIL LYMPHOCYTE RATIO AND LIPID PROFILE IN ADULT PATIENT WITH OBESITY IN PRODIA TANGERANG CLINICAL LABORATORY - Sari, Lia Dwi; Anak Agung Ayu Eka Cahyani; Ika Setya Purwanti (PT. Jurnal Center Indonesia Publisher, 2025)
Obesity is a condition of abnormal or excessive fat accumulation which can be a risk factor for dyslipidemia. Uncontrolled dyslipidemia can directly cause endothelial dysfunction by increasing the production of free radicals, causing Low Density Lipoprotein (LDL) oxidation and stimulating the release of inflammatory factors that can cause inflammation. Neutrophils and macrophages are the first leucocytes to appear in the early response to inflammation, so the neutrophil-lymphocyte ratio can be useful for evaluating the prognosis of inflammation as an early detector and as a marker of inflammation that can be detected simply and efficiently. This study aims to determine the correlation between Neutrophil-Lymphocyte Ratio (NLR) and Lipid Profile in adult patients with obesity in Prodia Tangerang Clinical laboratory. This study is an analytical study with a cross-sectional approach and used purposive sampling technique. The research sample data was taken from secondary data from patient medical records. The p-value obtained using Rank Spearman correlation from the comparation of neutrophil-lymphocyte ratio with each lipid profile value is total cholesterol (p=0.003), LDL cholesterol (p=0.013), High Density Lipoprotein (HDL) cholesterol (p=0.375) and tryglicerides (p=0.316). This study found a relationship between the neutrophil-lymphocyte ratio with total cholesterol dan LDL cholesterol, but there was no relationship between the neutrophil-lymphocyte ratio with HDL cholesterol and tryglicerides in obese adult patient in Prodia Tangerang Clinical Laboratory.